Microextraction Techniques Used in the Procedures for Determining Organomercury and Organotin Compounds in Environmental Samples - Rutkowska, Małgorzata (Molecules, 2014)
Due to human activities, the concentrations of organometallic compounds in all parts of the environment have increased in recent decades. The toxicity and some biochemical properties of mercury and tin present in the environment depend on the concentration and chemical form of these two elements. The ever-increasing demand for determining compounds at very low concentration levels in samples with complex matrices requires the elimination of interfering substances, the reduction of the final extract volume, and analyte enrichment in order to employ a detection technique, which is characterised by high sensitivity at low limits of quantification. On the other hand, in accordance with current trends, the analytical procedures should aim at the miniaturisation and simplification of the sample preparation step. In the near future, more importance will be given to the fulfilment of the requirements of Green Chemistry and Green Analytical Chemistry in order to reduce the intensity of anthropogenic activities related to analytical laboratories. In this case, one can consider the use of solvent-free/solvent-less techniques for sample preparation and microextraction techniques, because the use of the latter leads to lowering the quantity of reagents used (including solvents) due to the reduction of the scale of analysis. This paper presents an overview of microextraction techniques (SPME and LPME) used in the procedures for determining different chemical forms of mercury and tin.